Constraints to community empowerment: A study of communities around forests in Pelalawan Regency, Riau Province - Herman Herman; Indah Susilowati; Retno Sunu Astuti; Hardi Warsono (Universitas Merdeka Malang, 2023)
The empowerment of village communities around the forest is called the Plants of Life program by the Regulation of the Minister of Environment and Forestry Number P.12/Menlhk-II/2015 concerning Industrial Plantation Forest Development where the community is entitled to 20% of the HTI area. However, this is very contradictory to the community in Pelalawan Regency where empowerment through plants of life still adopts the pattern of giving cash. The purpose of this study is to analyze and explain the obstacles to empowering communities around the forest in Pelalawan Regency, Riau Province. This research uses a type of qualitative research with a case study approach that the author considers can answer the problems faced, namely related to obstacles to community empowerment around the forest. The type of research used is qualitative research with a case study approach. The data analysis techniques used are interview, observation, and documentation techniques. The informants in this study were the village government, community leaders, and the company. The data used consists of primary and secondary data. The results of the discussion show the lack of community ability to change from consumptive patterns to ideal empowerment patterns. Then existing institutions in the village such as teams/cooperatives are unable to accommodate the welfare of the community, as well as regulations that are unable to accommodate empowerment.